Banjo roots and branches - Winans, Robert B. (Music in American life., 2018)
The story of the banjo's journey from Africa to the western hemisphere blends music, history, and a union of cultures. This book presents scholarship that covers the instrument's West African origins and its adaptations and circulation in the Caribbean and United States. The contributors provide detailed ethnographic and technical research on gourd lutes and ekonting in Africa and the banza in Haiti while also investigating tuning practices and regional playing styles. Other essays place the instrument within the context of slavery, tell the stories of black banjoists, and shed light on the banjo's introduction into the African- and Anglo-American folk milieus. Wide-ranging and illustrated with twenty color images, this book offers information to scholars of African American and folk musics as well as the worldwide community of banjo aficionados. --